Design and research of a novel non-contact vertical inductive torque sensor. (June 2021) - Zhang, Chao; Li, Zhipeng; Chen, Jie; Qiu, Feng; Na, Shaodan
Highlights: A non-contact vertical torque sensor with small size and light weight is designed. Analyze the nonlinearity of the torque sensor according to different rotors. Establish a linear relationship between the output signal and the measured value. Experimental results show that the nonlinearity of the sensor is 1.36% F.S. Abstract: In this study, a new type of non-contact vertical inductive torque sensor was built and investigated. The sensor is small and easy to install and uses the principle of electromagnetic induction to measure the angular displacement of a rotor. More precisely, based on the relative displacement of the two rotors, the torque of the torsion bar is determined. Since the eddy-current distribution on the rotor surface is uneven, and the shape of the rotor affects the eddy-current path, four different shapes of the rotor are used for the analysis. Using Ansys Maxwell finite-element software, the change of the induced voltage of the sensor's receiving coil, when the torsion bar rotates, is simulated. Furthermore, the effect of different rotors on the nonlinear characteristics of the sensor is analyzed. Based on the simulation results, a prototype of the sensor is manufactured. The experimentally obtained nonlinearity is 1.36%F.S.